2001
DOI: 10.1177/152660280100800213
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Renal Artery Stenosis

Abstract: Significant changes have occurred in the treatment of renal artery disease over the past few years. Although excellent clinical results can be obtained with surgery, percutaneous transluminal renal angioplasty has proved similarly efficacious and is now the treatment of choice for nonostial atherosclerotic stenoses and fibromuscular dysplasia. The introduction of stents has become a valuable adjunctive therapy for postangioplasty restenosis and dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Renal artery angioplasty is without complication in the majority of cases. 1 A recent review of the renal angioplasty morbidity found that the incidence of arterial perforation or rupture was Ͻ1% in an analysis of 5 studies involving 879 patients. 1 Most postangioplasty complications, notably acute occlusion, dissection, and rupture, are either radiologically obvious at the time of the renal intervention or are clinically obvious soon after the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Renal artery angioplasty is without complication in the majority of cases. 1 A recent review of the renal angioplasty morbidity found that the incidence of arterial perforation or rupture was Ͻ1% in an analysis of 5 studies involving 879 patients. 1 Most postangioplasty complications, notably acute occlusion, dissection, and rupture, are either radiologically obvious at the time of the renal intervention or are clinically obvious soon after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…1 A recent review of the renal angioplasty morbidity found that the incidence of arterial perforation or rupture was Ͻ1% in an analysis of 5 studies involving 879 patients. 1 Most postangioplasty complications, notably acute occlusion, dissection, and rupture, are either radiologically obvious at the time of the renal intervention or are clinically obvious soon after the procedure. Renal artery rupture during angioplasty, which can occur at the lesion site or elsewhere owing to guidewire perforation, has been reported for renal atherosclerotic 2 and fibromuscular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The interventionist now has to decide whether to dilate or to stent the lesion. There is general agreement that ostial lesions should be stented as this improves primary patency rates and reduces the burden of reinterventions [15][16][17][18][19][20]. Arteries with fibromuscular dysplasia should be dilated only as restenoses rarely occur [19].…”
Section: Technique Of Renal Artery Pta and Stentingmentioning
confidence: 99%
“…Arteries with fibromuscular dysplasia should be dilated only as restenoses rarely occur [19]. Nonostial lesions may be primarily dilated [17][18][19], secondary stenting may be- Table 1. Indications for renal artery revascularization.…”
Section: Technique Of Renal Artery Pta and Stentingmentioning
confidence: 99%
“…1,2 During follow-up, most stent-related complications are restenosis. Only a few cases of renal stent fractures have been reported in the relevant literature.…”
mentioning
confidence: 99%